2005
DOI: 10.1128/aem.71.4.1717-1728.2005
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Recombinant Escherichia coli in High-Cell-Density Fermentations for Improved Production of an Antibody Fragment Biopharmaceutical

Abstract: By using two-dimensional polyacrylamide gel electrophoresis, a proteomic analysis over time was conducted with high-cell-density, industrial, phosphate-limited Escherichia coli fermentations at the 10-liter scale. During production, a recombinant, humanized antibody fragment was secreted and assembled in a soluble form in the periplasm. E. coli protein changes associated with culture conditions were distinguished from protein changes associated with heterologous protein expression. Protein spots were monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 41 publications
0
38
1
Order By: Relevance
“…Indeed, the heat-inducible and inorganic phosphorus-responsive promoters have been widely used in numerous laboratories (3,37,38,115,139). In addition, the genes encoding proteins that confer tolerances to acid, heat, and toxic substances have been successfully used for the improvement of cellular properties and enhanced degradation of toxic chemicals.…”
Section: Proteomics For Biotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the heat-inducible and inorganic phosphorus-responsive promoters have been widely used in numerous laboratories (3,37,38,115,139). In addition, the genes encoding proteins that confer tolerances to acid, heat, and toxic substances have been successfully used for the improvement of cellular properties and enhanced degradation of toxic chemicals.…”
Section: Proteomics For Biotechnologymentioning
confidence: 99%
“…Proteomic analysis has been used to directly monitor cellular changes occurring during the production of heterologous proteins in E. coli and develop efficient strains for the enhanced production of bioproducts (3,37,38,97,98,114,115,116,135,138,160,162,235,306) and biodegradable polymers (99,139). Furthermore, many of these proteomic studies have been performed in large-scale processes employing E. coli and recombinant E. coli for industrial applications (3,37,38,97,114,115,116,135,138,139,145,241,245,325). In addition, proteomic studies for analyzing the composition of inclusion bodies (IBs) (98,101,135,138,246,247) have been carried out in order to improve the quality (or uniformity) of the desired product and the downstream process of recombinant proteins such as protein purification and refolding.…”
Section: Proteomics For Biotechnologymentioning
confidence: 99%
“…Proteome analysis is also a powerful tool for systems-level analysis of whole cell proteins, even though it does not provide a true global picture owing to unknown proteins. It can be used to identify genes to be engineered to develop superior strains [29,30]. Proteome reference maps, which enable identification of proteins on 2D gel, are used for comparative proteome profiling [31][32][33][34].…”
mentioning
confidence: 99%
“…In E. coli, large-scale production of recombinant proteins including various antibodies has been successfully accomplished by high cell density cultivation (HCDC) technologies that can achieve cell densities higher than OD 600 of 100 [11,12]. Since Carter et al [13] first reported the production of 1-2 g/L of humanized F(ab) 2 in a 10 L culture of E. coli, HCDC of E. coli has been used for the production of many antibody fragments as well as full length IgG [14][15][16][17][18][19][20]. Horn et al [17] performed the fed-batch fermentation for the production of dimeric miniantibodies against EGF-receptor in 10 L bioreactor, and they could successfully produce more than 3 g/L of soluble antibodies, which is the best reported so far.…”
Section: Introductionmentioning
confidence: 99%